Estrategias de marketing en Comercial Don Jorge de la ciudad de Babahoyo. - Duarte Aguirre, Lastenia Mariuxi (2024)
Commercial Don Jorge, a company located in Babahoyo and owned by Mr. José Jorge Nauya Soria, has been in the grocery and daily consumer products market for more than 10 years. Known for its personalized service and quality products, it has maintained a loyal customer base. However, in recent years, the company has faced significant challenges due to increasing competition and lack of modern marketing strategies. Commercial Don Jorge's advertising has been based on traditional methods, which have managed to maintain an acceptable level of sales. However, these strategies have not been enough to compete with other supermarket chains that are nearby and use modernized techniques. The entry of new supermarket chains with competitive prices and value-added strategies has reduced customer loyalty towards Commercial Don Jorge. The use of brochures and posters has not been sufficient to attract new customers, and the absence of loyalty and retention strategies has resulted in a decrease in customer loyalty. This case study has identified these shortcomings and focuses on understanding and analyzing the internal problems of the organization. This research is justified by the need to take advantage of the opportunities of modern marketing to ensure the growth and sustainability of the company. In addition, this study can be useful for academic subjects of strategic planning and strategic marketing, contributing to the strengthening of the local economy and improving competitiveness.